Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/03069885.2020.1867703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing agency in career development via cognitive information processing theory

Abstract: The interconnected aspects of career and mental health posit career as a central feature of human functioning. A perceived lack of control within career and work exacerbates existing challenges associated with COVID-19. Focusing on enhancing agency within the realm of career and work is imperative within counselling. Cognitive Information Processing (CIP) accounts for the complexity of career concerns by enhancing agency in career decision making, with problem solving serving as a conduit between uncertainty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…It reminds individuals to concentrate on career development tasks and vocational transitions and decision-making in the proximal or distal future [11,12]. Different models of career development such as Social Cognitive Career Theory, Career Construction Theory, and Cognitive Information Process Theory have considered career concern to be planfulness, anticipation, awareness, involvement, and orientation [10,13,14]. If an individual lacks career concern, this may reflect career indifference, which reflects planlessness and pessimism about his/her future career [15].…”
Section: Career Concernmentioning
confidence: 99%
“…It reminds individuals to concentrate on career development tasks and vocational transitions and decision-making in the proximal or distal future [11,12]. Different models of career development such as Social Cognitive Career Theory, Career Construction Theory, and Cognitive Information Process Theory have considered career concern to be planfulness, anticipation, awareness, involvement, and orientation [10,13,14]. If an individual lacks career concern, this may reflect career indifference, which reflects planlessness and pessimism about his/her future career [15].…”
Section: Career Concernmentioning
confidence: 99%
“…Prior scholarly literature (Dozier et al., 2016; Hayden et al, 2021; Rottinghaus et al., 2020) suggested that practitioners adopt a more holistic approach to client career concerns, which may intersect with mental health and personality factors (Lewis & Cardwell, 2020; Vyakarnam, 2019). Research connecting these factors can help inform more holistic approaches to student and client concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating factors that impact career decision‐making, such as career thoughts, have been an area of interest in recent years (e.g., Andrews, 2014; Atta et al., 2013; Finklea, 2016; Hechtlinger, et al., 2019). Furthermore, negative career thoughts and career indecision have been correlated with mental health factors including depression (Buzzetta et al., 2020; Dieringer et al., 2017; Walker & Peterson, 2012), anxiety (Poler, 2010), worry (Hayden et al, 2021), and meaning in life (Buzzetta et al., 2020). Understanding relationships between personality and various career constructs may enhance the practice of integrating research findings and theories when providing services to clients (Rottinghaus et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Career/employment insecurity can be defined as an individual's overall concern regarding the attainment, continuity, and stability of one's career or employment manifesting, for example, as worries about career decision‐making, entrance to the workforce, and job loss or unemployment (see De Witte et al, 2016; Hayden et al, 2021; Karamessini et al, 2019; Sampson et al, 1998; Shoss, 2017; Spurk et al, 2016, 2022). Career/employment insecurity can be a notable stressor for individuals in today's turbulent labor market (De Witte et al, 2016; Shoss, 2017; Sverke et al, 2002, 2019), particularly for young people because they often lack work experience, making them more susceptible to feelings of insecurity (Karamessini et al, 2019; Klug, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ECI might be a particular concern in increasingly dynamic work‐life contexts (Hirschi & Koen, 2021; Spurk et al, 2016). Nowadays, young individuals have to navigate their educational and career paths in often unpredictable and fast‐changing environments characterized by occupational erosion due to rapid technological development and by difficulties in forecasting what sorts of vocational skills and competences will be needed in future working life (Ferrari et al, 2018; Gati & Kulscár, 2021; Hayden et al, 2021; Hirschi & Koen, 2021; Hoff et al, 2022; Khattab et al, 2022; Klug, 2020). Also, contemporary career theories, e.g., cognitive information processing theory (CIP; Osborn et al, 2013; Sampson et al, 2004), which focus on career decision‐making and insecurity in transition stages, underscores the external contextual factors underlying career decisions and actions.…”
Section: Introductionmentioning
confidence: 99%